2020
DOI: 10.1186/s12866-020-02034-9
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipids and surfactin inhibit the growth or formation of oral bacterial biofilm

Abstract: Background Bacteria survive in various environments by forming biofilms. Bacterial biofilms often cause significant problems to medical instruments and industrial processes. Techniques to inhibit biofilm formation are essential and have wide applications. In this study, we evaluated the ability of two types of biosurfactants (rhamnolipids and surfactin) to inhibit growth and biofilm formation ability of oral pathogenic bacteria such as Aggregatibacter actinomycetemcomitans, Streptococcus mutans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…As in the case of any other biological processes, one can identify positive and negative aspects of biofilm formation for human life. For example, bacterial biofilms are crucial for effective functions of microbial fuel cells, for efficient production of various products during fermentation, and for biological stages of wastewater treatment [ 4 ]. However, pathogenic bacteria can form biofilms on surfaces of various materials used in medicine, as well as on surfaces of patients’ tissues [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of any other biological processes, one can identify positive and negative aspects of biofilm formation for human life. For example, bacterial biofilms are crucial for effective functions of microbial fuel cells, for efficient production of various products during fermentation, and for biological stages of wastewater treatment [ 4 ]. However, pathogenic bacteria can form biofilms on surfaces of various materials used in medicine, as well as on surfaces of patients’ tissues [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, at a surfactin concentration of 0.625% w/v, growth inhibition of Staphylococcus epidermidis was recorded ( Abdelli et al, 2019 ). Recently, surfactin has been reported to inhibit growth of specific oral pathogens, particularly S. sanguinis ATCC105566 at concentrations of > 1.26 × 10 –3 w/v% ( Yamasaki et al, 2020 ), and removal of biofilms of Legionella pneumophila (6.6 × 10 –3 w/v% of surfactin) ( Loiseau et al, 2015 ). In addition, surfactin is also reported to remove stainless steel and polypropylene surface biofilm of Listeria monocytogenes, Enterobacter sakazakii , and Salmonella enteritidis ( Yamasaki et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surfactin from Bacillus circulans is an example of a propitious lipopeptide with antimicrobial property ( Das et al, 2008 ). A recently published research article demonstrated antibiofilm property of two biosurfactants (rhamnolipids and surfactin) ( Yamasaki et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, RLs produced by P. aeruginosa significantly inhibited the growth of S. mutans UA159 and S. sanguinis ATCC10556. Furthermore, they completely inhibited the growth of Aggregatibacter actinomycetemcomitans Y4 at high concentrations [ 7 ].…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Recently, the production of SACs has received extensive attention because of their diverse applications, such as dissolving water-insoluble compounds, heavy metal binding, contaminant desorption, inhibiting bacterial pathogenesis, adhesion, and cell aggregation [ 4 , 5 , 6 , 7 , 8 ]. In addition, SACs also have several advantages over synthetic surfactants, such as low toxicity, lower critical micelle concentration (CMC), higher biodegradability, and ecological acceptability [ 9 ].…”
Section: Introductionmentioning
confidence: 99%